Peptides as Quorum Sensing Molecules: Measurement Techniques and Obtained Levels In vitro and In vivo - Verbeke, Frederick; De Craemer, Severine; Debunne, Nathan; Janssens, Yorick; Wynendaele, Evelien; Van de Wiele, Christophe; De Spiegeleer, Bart (Frontiers in Neuroscience, 2017)
The expression of certain bacterial genes is regulated in a cell-density dependent way, a phenomenon called quorum sensing. Both Gram-negative and Gram-positive bacteria use this type of communication, though the signal molecules (auto-inducers) used by them differ between both groups: Gram-negative bacteria use predominantly N-acyl homoserine lacton (AHL) molecules (autoinducer-1, AI-1) while Gram-positive bacteria use mainly peptides (autoinducer peptides, AIP or quorum sensing peptides). These quorum sensing molecules are not only involved in the inter-microbial communication, but can also possibly cross-talk directly or indirectly with their host. This review summarizes the currently applied analytical approaches for quorum sensing identification and quantification with additionally summarizing the experimentally found in vivo concentrations of these molecules in humans.